Indocyanine Green Fluorescence for Liver Assessment and Imaging-Guided Resection of Colorectal Metastases: A Case Report - Arabadzhieva E.; Bonev S.; Bulanov D.; Simonova L.; Zhivkov E.; Korukov G.; Shavalov Zh.; Velizarova M.; Svinarov D.; Yonkov A. (Acta Medica Bulgarica, 2023)
Liver resection is widely accepted as a treatment option for primary liver cancer and metastases. The goal of surgery is to resect all tumours with negative histological margins while preserving sufficient functional hepatic parenchyma and reducing postoperative complications. The use of Indocyanine green (ICG) for liver function assessment and fluorescence image-guided surgery could be used to achieve that goal.